The Play in the System The Art of Parasitical Resistance - Fisher, Anna Watkins (Duke University Press, 2020)
What does artistic resistance look like in the twenty-first century, when disruption and dissent have been co-opted and commodified in ways that reinforce dominant systems? In The Play in the System Anna Watkins Fisher locates the possibility for resistance in artists who embrace parasitism-tactics of complicity that effect subversion from within hegemonic structures. Fisher tracks the ways in which artists on the margins-from hacker collectives like Ubermorgen to feminist writers and performers like Chris Kraus-have willfully abandoned the radical scripts of opposition and refusal long identified with anticapitalism and feminism. Space for resistance is found instead in the mutually, if unevenly, exploitative relations between dominant hosts giving only as much as required to appear generous and parasitical actors taking only as much as they can get away with. The irreverent and often troubling works that result raise necessary and difficult questions about the conditions for resistance and critique under neoliberalism today.